The soft story challenge to architectural design in earthquake-prone areas - Teddy, Livian; Hardiman, Gagoek; Nuroji,; Tudjono, Sri (Penerbit Universiti Kebangsaan Malaysia, 2018)
The stiffness of irregular configurations/soft storeys is the most frequent cause of structural failure in the irregular vertical part of a building when major earthquakes occur in Indonesia, leaving behind many victims. Soft storeys occur because the first floor of a building is usually more flexible than the other floors. When a strong earthquake occurs, the more flexible storey is not strong enough to withstand the force of the earthquake, and it will cause the building to break and collapse. This paper attempted to address the structural failure of the soft storey, particularly in Indonesia, with regard to its causes, and to find ways to evaluate it and to overcome it through architectural designs. Therefore, this can be taken into consideration by architects in their designing process. The research involved a literature review of topics on soft storeys from existing books and researches. Based on the study, the occurrence of soft storeys in Indonesia is due to inadequate shear column capacity, the presence of a weak storey, a significant difference in wall densities between the floors, the use of materials with different degrees of stiffness in the main structure, structural ductility and poor construction. To reduce the potency of soft storeys, several things can be done by architects in their designing processes such as avoiding direct contact between brick walls, columns and beams, increasing the shear capacity of columns by 2.5 times the normal calculation, using shear walls on the first floor, installing bracings and using seismic insulations